Comparison of body cooling methods on physiological and perceptual measures of mildly hyperthermic athletes - DeMartini, J. K.; Ranalli, G. F.; Casa, D. J.; Lopez, R. M.; Ganio, M. S.; Stearns, R. L.; McDermott, B. P.; Armstrong, L. E.; Maresh, C. M. (The Journal of Strength and Conditioning Research, 2011)
Hyperthermia is common among athletes and in a variety of environments. The purpose of this study was to evaluate the effectiveness of cooling methods on core body temperature, heart rate (HR), and perceptual readings in individuals after exercise. Sixteen subjects (age: 24 ± 6 years, height: 182 ± 7 cm, weight: 74.03 ± 9.17 kg, and body fat: 17.08 ± 6.23%) completed 10 exercise sessions in warm conditions (WBGT: 26.64 ± 4.71°C) followed by body cooling by 10 different methods. Cooling methods included cold water immersion (CWI), shade, Port-a-Cool® (FAN), Emergency Cold Containment System® (ECCS), Rehab. Hood® (HOOD), Game Ready Active Cooling Vest™ (GRV), Nike Ice Vest™ (NIV), ice buckets (IBs), and ice towels (IT). These cooling modes were compared with a control (SUN). Rectal temperature (Tre), HR, thermal sensation, thirst sensation, and a 56-question Environmental Symptoms Questionnaire (ESQ) were used to assess physiological and perceptual data. Average Tre after exercise across all trials was 38.73 ± 0.12°C. After 10 minutes of cooling, CWI (-0.65 ± 0.29°C), ECCS (-0.68 ± 0.24°C), and IB (-0.74 ± 0.34°C) had significantly (p < 0.006) greater decreases in Tre compared with that in SUN (-0.42 ± 0.15°C). The HR after 10 minutes of cooling was significantly (p < 0.006) lower for CWI (82 ± 15 b/min), ECCS (87 ± 14 b/min), and IT (84 ± 15 b/min) when compared with SUN (101 ± 15 b/min). The thermal sensation between modalities was all significantly (p < 0.006) lower (CWI: 1.5 ± 0.5; Fan: 3.0 ± 1.0; ECCS: 4.5 ± 1.0; Hood: 4.5 ± 0.5; GRV: 4.0 ± 0.5; NIV: 4.5 ± 1.0; IB: 4.0 ± 1.0; IT: 3.0 ± 1.0) when compared with SUN (5.5 ± 0.5), except for Shade (5.0 ± 1.0). There were no significant differences (p > 0.006) in thirst sensation between modalities. The ESQ scores were significantly (p < 0.006) lower for CWI (1 ± 6), Fan (4 ± 5), and IT (3 ± 8) compared with that for SUN (13 ± 12). In conclusion, when athletes experience mild hyperthermia, CWI, ECCS, and IB resulted in a significantly greater decrease in Tre. These cooling strategies are recommended to decrease Tre during a brief recovery period between exercise bouts.